Changes in the distribution of elements in the liver and various brain regions in suicides from southeastern Poland - Jacek Baj; Alicja Forma; Kaja Karakuła; Wojciech Flieger; Michał Flieger; Beata Kowalska; Iwona Kamińska; Dariusz Majerek; Grzegorz Teresiński; Ryszard Maciejewski; Elżbieta Radzikowska-Büchner; Jolanta Flieger (Scientific Reports)
Abstract The anthropogenic environment and diet are sources of chemical elements, both essential and toxic. Many of them play a key role in the proper functioning of the brain by controlling oxidative metabolism, neurotransmission and the production of neurotransmitters. Disturbances in element homeostasis are associated with the development of depression and many neurodegenerative diseases. The study examined the content of several elements in liver and brain samples taken from autopsies of residents of south-eastern Poland (n = 40). In order to determine the differences in the elemental composition of tissues collected from suicide victims compared to the control group who died from another cause, the Mann-Whitney U test was performed. There was a significant difference in the correlation patterns between the two groups for both brain (χ² = 1490.19, df = 1378, p < 7e-122, z = 3.72) and liver χ² = 2998.7, df = 1378, p < 0.018, z = 126.71). Two-way non-parametric Spearman rank correlation matrices showed different numbers and strengths of correlations for most brain regions in the compared groups, especially for the head of the caudate nucleus (Latin: caput nuclei caudati), superior longitudinal fasciculus (Latin: fasciculus longitudinalis superior cerebri), and hippocampus (Latin: hippocampus). Differences between groups reached statistical significance in the case of higher lanthanide content in the liver of suicides and lower Ca content in the basal ganglia (head of the caudate nucleus, nucleus accumbens septum), dorsal thalamus and insula. Brain samples from different regions of suicide victims were characterized by higher levels of, among others: Ag, P, Fe and Cu. Our findings suggest clear differences in trace metal content and inter-correlations in the brain and liver tissues of suicide victims compared to controls.